Effect of cerebral oxygen saturation monitoring in patients undergoing superficial temporal anterior-middle cerebral artery anastomosis for ischemic Moyamoya disease: a prospective cohort study - Chen, Xuanling; Qin, Xuewei; Wang, Jing; Wang, Rong; Guo, Xiangyang; Yao, Lan (Frontiers in Neurology, 2023)
Objective Regional cerebral oxygen saturation (rSO2) is linked with blood pressure. This study evaluated the influence of perioperative rSO2 monitoring on the prognosis of ischemic Moyamoya disease (MMD) patients undergoing anastomosis surgery. Methods In this prospective cohort, patients with unilateral ischemic MMD of Suzuki stage ≥3 were included. The decision of rSO2 was made by the clinician and the patient. The rSO2 group maintained intraoperative rSO2 levels through the modulation of blood pressure, inhaled oxygen concentration, carbon dioxide in arterial blood, and red blood cell transfusion. The non-rSO2 group used conventional anesthesia practices. Perioperative mean arterial pressure (MAP), rSO2 values, neurological complications, and postoperative results were assessed. Results A total of 75 eligible patients were categorized into a rSO2 monitoring group (n = 30) and a non-rSO2 monitoring group (n = 45). For the rSO2 group, the preoperative rSO2 was significantly lower on the affected side (P < 0.05). After anastomosis, this value notably increased (P = 0.01). A moderate relationship was observed between perioperative rSO2 and MAP before, during, and after surgery, with correlation coefficients (r) of 0.536, 0.502, and 0.592 (P < 0.05). Post-surgery MAP levels differed between the groups, with the rSO2 group showing decreased levels compared to pre-surgery and the non-rOS2 group displaying elevated levels. Notably, the rSO2 group reported shorter hospitalizations and decreased neurological complications. Patients with a hypertension history found postoperative MAP influencing hospital stay duration. Conclusion Perioperative rSO2 surveillance enhanced cerebral perfusion and minimized postoperative complications in ischemic MMD patients. Thus, rSO2 monitoring is advocated for MMD patients undergoing vascular anastomosis.